Kebijakan Kriminal Penanggulangan Tindak Pidana Ekonomi di Indonesia - Iza Fadri (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research focuses on the eradication of economic crimes policy in Indonesia. This is a normative juridical research using statute approach and conceptual approach. Legal materials collected by literary study which is analyzed qualitatively. This research found that eradication of economic crime policy as public policy to solve economic crime is still focused on the effort of criminalization through legislation dan legal enforcement using criminal justice system, in which non-criminal justice sistem actors still do not perform well in eradication of economic crime through preventive action.Key words : Criminal Policy, economics crime, and law enforcement